IPTF Survey for Cool Transients. (1st February 2018) - Adams, S. M.; Blagorodnova, N.; Kasliwal, M. M.; Amanullah, R.; Barlow, T.; Bue, B.; Bulla, M.; Cao, Y.; Cenko, S. B.; Cook, D. O.; Ferretti, R.; Fox, O. D.; et al.
Abstract: We performed a wide-area (2000 deg 2 ) g and I band experiment as part of a two month extension to the Intermediate Palomar Transient Factory. We discovered 36 extragalactic transients including iPTF17lf, a highly reddened local SN Ia, iPTF17bkj, a new member of the rare class of transitional Ibn/IIn supernovae, and iPTF17be, a candidate luminous blue variable outburst. We do not detect any luminous red novae and place an upper limit on their rate. We show that adding a slow-cadence I band component to upcoming surveys such as the Zwicky Transient Facility will improve the photometric selection of cool and dusty transients.